Pseudomonas Fluorescent As A Biocontrol Agent Against Plant Pathogens - Dilla, Aprina; Advinda, Linda; Handayani, Dezi; Chatri, Moralita (Department of Biology, Faculty of Mathematics and Natural Sciences, Universitas Negeri Padang, 2024)
The use of biological control agents as alternatives to synthetic fungicides is increasingly being developed as farmers become more aware of the negative effects of synthetic fungicides. Various biocontrol agents have been developed from several bacteria that are very effective against plant diseases, including pseudomonas fluorescent. The mechanism of bacterial inhibition against pathogens can take place through several ways, namely colonization, competition and antibiosis. Pseudomonas fluorescent is able to produce secondary metabolite compounds such as siderophores, HCN, antibiotics, enzymes that can inhibit the growth and development of pathogens and can induce systemic resistance.